The introduction of a regional Norwegian HEMS coordinator: an assessment of the effects on response times, geographical service areas and severity scores - Ole Erik Ulvin; Eivinn Årdal Skjærseth; Helge Haugland; Kjetil Thorsen; Trond Nordseth; Marie Falch Orre; Lars Vesterhus; Andreas Jørstad Krüger (BMC, 2022)
Abstract Background Due to unwanted delays and suboptimal resource control of helicopter emergency medical services (HEMS), regional HEMS coordinators have recently been introduced in Norway. This may represent an unnecessary link in the alarm chain, which could cause delays in HEMS dispatch. Systematic evaluations of this intervention are lacking. We wanted to conduct this study to assess possible changes in HEMS response times, mission distribution patterns and patient characteristics within our region following this intervention. Methods We retrospectively collected timeline parameters, patient characteristics and GPS positions from HEMS missions executed by three regional HEMS bases in Mid-Norway during 2017-2018 (preintervention) and 2019 (postintervention). The mean regional response time in HEMS missions was assessed by an interrupted time series analysis (ITS). The geographical mission distribution between regional HEMS resources was assessed by a before-after study with a convex hull-based method. Results There was no significant change in the level (-0.13 min/month, p = 0.88) or slope (-0.13 min/month, p = 0.30) of the mean regional response time trend line pre- and postintervention. For one HEMS base, the service area was increased, and the median mission distance was significantly longer. For the two other bases, the service areas were reduced. Both the mean NACA score (4.13 ± SD 0.027 vs 3.98 ± SD 0.04, p < 0.01) and the proportion of patients with severe illness or injury (NACA 4-7, 68.2% vs 61.5%, p < 0.001) were higher in the postintervention group. Conclusion The introduction of a regional HEMS coordinator in Mid-Norway did not cause prolonged response times in acute HEMS missions during the first year after implementation. Higher NACA scores in the patients treated postintervention suggest better selection of HEMS use.